Active volcanoes of Kamchatka and Northern Kurils in 2005 - Girina O.A.; Manevich A.G.; Malik N.A.; Melnikov D.V.; Ushakov S.V.; Demyanchuk Yu.V.; Kotenko L.V. (My University, 2007)
In 2005, six major eruptions of four Kamchatka volcanoes (Bezymyannyi, Klyuchevskoy, Shiveluch, and Karymskii) occurred and the Avachinskii, Mutnovskii, and Gorelyi Kamchatka volcanoes and the Ebeko and Chikurachki volcanoes in northern Kurils were in a state of increased activity. Owing to a close collaboration between the KVERT project, Elizovo airport meteorological center, and volcanic ash advisory centers in Tokyo, Anchorage, and Washington (Tokyo, Anchorage, and Washington VAACs), all necessary measures for safe airplane flights near Kamchatka were taken and fatal accidents related to volcanic activity did not occur.
Keywords: 38.37.25 Вулканология; Безымянный; Шивелуч; Ключевской